Building a Cloud Computing Platform for New Possibilities. - Khalidi, Yousef A. (Computer (00189162), 2011)
Cloud computing represents a drastic shift, both in terms of the amazing new economics it brings to bear and in terms of the new possibilities it enables. At the platform level, the cloud delivers unprecedented benefits, including global scale on an as-needed basis, protection against hardware and software failures, and a rich set of services like storage, relational database management services, queuing, caching, and more. Realizing the full benefits of this new paradigm will require rethinking the way developers build applications. Because it will take time for practice to catch up with technology, we must have a disciplined and thoughtful approach to embracing hybrid models.